What Next? - Ayodele-Bamisaye Oluremi (Macmillan Nigeria Publishers Ltd, 2001)
The village of Agugu is very proud of Hassan, a.k.a. "De Gov", a young ECOMOG soldier who has just returnedfrom Liberia with lots of Diamonds. The Chief dreams of Hassan becoming a governor one day, and his love affair with Aishat further confirms this plan. Hassan and Aishat are engaged to be married. Aishat goes to Secondary School while Hassan returns to Liberia... But will they ever marry?
Keywords: Juvenile Fiction / Realistic / What Next